Intertemporal stability of ambiguity preferences - Peter Duersch; Daniel Römer; Benjamin Roth (University of Heidelberg, Department of Economics, 2013)
To make predictions with theories, usually we assume an individual's characteristics such as uncertainty preferences to be stable over time. In this paper, we analyze the stability of ambiguity preferences experimentally. We repeatedly elicit ambiguity attitudes towards multiple 3-color Ellsberg urns over a period of two months. In our data, 57% of the choices are consistent with stable preferences over the time of observation. This share is significantly higher than random choices would suggest, but significantly lower than the level of consistency in a control treatment without a time lag (71%). Interestingly, for subjects who are able to recall their decision after two months correctly, the share of consistent choices does not drop significantly over time.
urn:nbn:de:bsz:16-heidok-154005
Keywords: 330; ambiguity; stability of preferences; experiment